Just friends [videorecording (DVD)] - Kumble, Roger; Reynolds, Ryan; Smart, Amy, 1976-; Faris, Anna, 1976- (New Line Home Entertainment, 2006)
During their high school years, Chris confessed his love for his best friend and was met with a broken heart and degrading humiliation. Adding insult to injury, Chris was a big guy and was a source of ridicule for cruel classmates. Years later things have changed and Chris is now a hotshot record producer in Hollywood and the complete physical opposite of himself in high school. When a freak accident occurs on the way to Paris, Chris is forced to return home with Samantha James, an up and coming act in tow. Little does he know that he would come face to face with the friend that he tried so desperately to forget. With the chance to woo her again, Chris will do what he can despite his client's violent misgivings and a competitive rival suitor against him. No matter the crazy obstacles he must overcome, Chris will do whatever it takes to be more than just friends.